A new species of the genus Mongolotettix Rehn, 1928 from Jiangxi, China (Acrididae, Acridoidea, Orthoptera) - Zhang, Da-Peng; Dai, Li; Yin, Zhan (Zootaxa, 2023)
The grasshopper genus Mongolotettix Rehn, 1928 obtains 17 species distributed from the Far Eastern Asian countries, including China, Japan, Korea, Mongolia, and Russia [Bolívar, 1898; Uvarov, 1914; Caudell, 1921; Chogsomzhav, 1974; Li et Lian, 1994; Wan, Ren et Zhang, 1998; Xie et Li, 2000; Kim et Kim 2005; Shi et al, 2016; Shi et al, 2017; Yin et al, 2017; Zheng et al, 2017; Chen et al, 2018; Zhang et al, 2020; Cigliano et al, 2022, Shen et al, 2022]. In the present paper, we describe a new species of the genus from Jiangxi, China. Type specimens are deposited in the Shanghai Entomological Museum, Chinese Academy of Sciences, Shanghai, 200032, China.